(untitled) (MAUSAM, 1979)
Using mean monthly values or the relative global, solar radiation, Qm/QC, and the relative duration of sunshine, n/N, the least square regression constants a and b in equation Qm/QC =a+6 (n/N) and the correlation coefficient r have been calculated for Mehrabad, Tehran (a=0.25, b=0,48, r=0.90), Karadj (a=0, 38,b=0.35, r=0.79), and also for Mehrabad (Tehran) and Karadj collectively (a=0.30,b=0.43, r=0.84),Qm and Qc being the daily global solar radiation received by one square centimetre of horizontal surface measured on the earth and calculated for the top of the atmosphere, respectively, and n and N the actual and the possible maximum duration of sunshine respectively. It is seen that the sum a + b remains constant. Furthermore, the ratio (Qm/Qc)M/(Qm/Qc )K is considered for clear days, where M and K stand for Mehrabad and Karadj stations. The ratio is generally less than unity, indicating that less radiation is normally received in Mehrabad (Tehran) compared to Karadj in a clear day.